SNAREs Regulate Vesicle Trafficking During Root Growth and Development - Luo, Changxin; Shi, Yumei; Xiang, Yun (Frontiers in Plant Science, 2022)
SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins spontaneously assemble to drive the final membrane fusion step of membrane trafficking. Thus, SNAREs are essential for membrane fusion and vesicular trafficking, which are fundamental mechanisms for maintaining cellular homeostasis. In plants, SNAREs have been demonstrated to be located in different subcellular compartments and involved in a variety of fundamental processes, such as cytokinesis, cytoskeleton organization, symbiosis, and biotic and abiotic stress responses. In addition, SNAREs can also contribute to the normal growth and development of Arabidopsis. Here, we review recent progress in understanding the biological functions and signaling network of SNAREs in vesicle trafficking and the regulation of root growth and development in Arabidopsis.